2013
DOI: 10.1002/cssc.201300143
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Cellulose Solvating Capabilities of Acid–Base Conjugate Ionic Liquids

Abstract: Different acid-base conjugates were made by combining a range of bases and superbases with acetic and propionic acid. Only the combinations that contained superbases were capable of dissolving cellulose. Proton affinities were calculated for the bases. A range, within which cellulose dissolution occurred, when combined with acetic or propionic acid, was defined for further use. This was above a proton affinity value of about 240 kcal mol(-1) at the MP2/6-311+G(d,p)//MP2/ 6-311+G(d,p) ab initio level. Understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
165
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 131 publications
(175 citation statements)
references
References 31 publications
9
165
1
Order By: Relevance
“…The ionic liquid [DBNH][OAc] was prepared from glacial acetic acid and DBN according to Parviainen et al (2013) with slight modifications: The reaction was performed in a two necked flask with a reflux condenser, under argon atmosphere and stirred magnetically. The superbase DBN (168.5 g, 1.3 mol) was measured to the flask and one equivalent of acetic acid (81.5 g, 1.3 mol) was weighed to a dropping funnel.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The ionic liquid [DBNH][OAc] was prepared from glacial acetic acid and DBN according to Parviainen et al (2013) with slight modifications: The reaction was performed in a two necked flask with a reflux condenser, under argon atmosphere and stirred magnetically. The superbase DBN (168.5 g, 1.3 mol) was measured to the flask and one equivalent of acetic acid (81.5 g, 1.3 mol) was weighed to a dropping funnel.…”
Section: Methodsmentioning
confidence: 99%
“…The chemical properties of ILs vary according to the composition. For instance, the ability to dissolve cellulose is often dependent on the basicity of the IL (Fukaya et al 2006(Fukaya et al , 2008King et al 2012;Parviainen et al 2013), but there are exceptions, e.g., tetraalkylphosphonium salts Holding et al 2014), which are basic but require a dipolar aprotic co-solvent to dissolve cellulose. In previous literature, the use of imidazolium based ILs, with alkyl substituents (ethyl, methyl, and allyl) and chloride, bromide or acetate anions, typifies most publications on cellulose dissolving ILs (Heinze et al 2008;Swatloski et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kamlet-Taft solvent parameters have been used to measure the ability of a solvent to donate a hydrogen bond (α), and accept a hydrogen bond (β) (51). It has been shown that basicity (β) correlates well with an IL's ability to dissolve lignocellulose (52), and that net basicity correlates with an IL's ability to dissolve cellulose (46,53). A recent experimental study on a range of cations in combination with the same anion demonstrated that cation acidity is also important for cellulose dissolution (54) PO 4 ], one would expect the differential substitution of the electron-donating groups to affect the N atom's affinity for the H 3 PO 4 proton.…”
Section: Compositional Analysis Of Untreated and Pretreated Switchgrassmentioning
confidence: 99%